2013
DOI: 10.1080/02642069.2013.719887
|View full text |Cite
|
Sign up to set email alerts
|

Buying impulse triggered by digital media

Abstract: This study applies Beatty and Elizabeth Ferrell's impulse buying model to investigate consumers' buying impulses after receiving digital media promotions for limited-timeonly sale for services. The influences of consumers' positive affect and impulse buying tendency on their felt urge to buy impulsively were explored. Questionnaires were utilized to survey consumers and structural equation modeling was adopted to explore the causal relationship among the constructs. The results indicated that consumers generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Scarcity is actually the strategic limitation of time, product supply, or any other purchase condition related to the product that passes a message to consumers about the low possibility to buy the desirable product (Aggarwal et al, 2011). The promotional messages on the internet about the supply of products indicate that there is limited availability of product or the product is only accessible within a particular time limit that generate a strong positive impact on consumers (Lin & Lin, 2013). The scarcity messages attract consumers to buy products and services that have a very limited time period (Chung et al, 2017).…”
Section: Scarcity Messagesmentioning
confidence: 99%
“…Scarcity is actually the strategic limitation of time, product supply, or any other purchase condition related to the product that passes a message to consumers about the low possibility to buy the desirable product (Aggarwal et al, 2011). The promotional messages on the internet about the supply of products indicate that there is limited availability of product or the product is only accessible within a particular time limit that generate a strong positive impact on consumers (Lin & Lin, 2013). The scarcity messages attract consumers to buy products and services that have a very limited time period (Chung et al, 2017).…”
Section: Scarcity Messagesmentioning
confidence: 99%
“…Prior studies determine that consumers are different in acting impulsively, produce unplanned and unintentional response to stimuli due to their impulse buying tendencies (Amos et al Lin and Lin (2013) found a significant relationship between consumers' impulse buying tendency and UBI. The association between consumers' tendency to impulse purchase and UBIin online context has also been studied in comparison with offline shopping context (Xiang et al 2016).…”
Section: Impulse Buying Tendencymentioning
confidence: 99%
“…The limited duration people can use is also known as time pressure [21]. The longer the group purchase time, the less time pressure consumers feel and the more positive emotions consumers will have, and the more time consumers have to choose [22], The greater the pressure of time, the more aggressive the consumer's Internet buying propensity is to increase [23]. Based on the temporal interpretation hierarchy theory, the mechanism of the subjective evaluation of events changing over time is discussed, which provides a basis for human rational decision-making, and the use of specific psychological models for the representation of future events of near time, ie low-level interpretation.…”
Section: B Research Hypothesis 1) Discount Ratementioning
confidence: 99%